Pengaruh Capital Intensity, Likuiditas dan Prinsip Kewajaran & Kelaziman Usaha Terhadap Manajemen Perpajakan: (Studi Pada Emiten Sektor Tambang Bursa Efek Indonesia Periode 2020-2022) - Sevtianti, Lola Serly; Rely, Gilbert; Prayogo, Bambang; Mulyadi; Hasioan Sianipar, Panata Bangar (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2024)
The study aims to examine the effect of Capital Intensity, Liquidity and Arm's Length Principle on Tax Management. The population of mining sector issuers on the Indonesia Stock Exchange for the 2020-2022 period. The research used quantitative data, multiple linear regression, sampling techniques namely purposive sampling methods and obtained as many as 10 issuers and 30 data samples. Hypothesis testing with SPSS Statistics 27, the results concluded that (1) Capital Intensity had no affect on Tax Management, (2) Liquidity had no affect on Tax Management, (3) Arm's Length Principle have a significant positive effect on Tax Management, (4) Capital Intensity, Liquidity and Arm's Length Principle simultaneously have a significant effect on Tax Managemen.